Forensic science and criminal justice: An analysis of curricular models - Lindquist, Charles A. (American journal of criminal justice, 1982)
The multi-disciplinary field of forensic science frequently finds its academic home within criminal justice programs. After examining the reasons for this academic linkage, an analysis of criminal justice curricular models and courses was undertaken to assess their applicability to forensic science education and careers. The authors concluded that the relationship between criminal justice and forensic science can be mutually beneficial; however, most criminal justice programs do not provide adequate preparation for meaningful careers in forensic science.